Heat transfer and Electric field Impacts on Ferrofluid Flow Over a Wedge - Loganayagi, V.; Kameswaran, Peri K. (Discontinuity, Nonlinearity, and Complexity, 2026)
The interest behind this article is to examine the electrohydrodynamic number, and heat transfer impacts on two dimensional, laminar, incompressible nanofluid boundary layer flow over a wedge. The well-known nanoparticle volume fraction model was applied to approximate the viscosity, thermal diffusivity, heat capacitance, and thermal conductivity of the nanofluid. The nanoparticles itemized here are Nickel, Ni, and Nickel Zinc Ferrite Ni(Zn)O.Fe_2O_3 with base liquid as water (Liquid H_2O). The governing system of equations is reduced in the system of nonlinear differential equations and solved numerically using MATLAB. The impact of the electrohydrodynamic parameter k_1, nanoparticle volume fraction φ, electric field functions g_1 on the velocity profile, the influence of the Prandtl number Pr, joule heating energy parameter s_2, and ion kinetic work parameter s_3 on temperature profile has examined. Further surface drag forces and the rate of heat transfer are inspected. A comparison is made with the available outcomes in the literature and present outcomes is a satisfactory concurrence with the findings in the literature for particular values. The velocity profile increases with an increase in electrohydrodynamic number, and also increases more in the case of Nickel than Nickel Zinc Ferrite. A decreasing trend in the velocity profile is observed for increasing values of electric field functions in both types of nanofluids. The temperature rises more in Nickel Zinc Ferrite than Nickel for an increase in the ion kinetic parameter. The cumulative effect of nanoparticle volume fraction and electric field function leads to decreases the heat transfer rate.